Issues in Clay: Western Canadian Sculpture. - Students' Union Art Gallery, University of Alberta, Edmonton; Alberta College of Art Gallery, Calgary; Medicine Hat Museum and Art Gallery (Edmonton : Latitude 53 Society of Artists, 1982)
Barbier, Sally ; Beug, Lorne ; Beauparlant, Luc ; Chalke, John ; Cicansky, Vic ; Fafard, Joe ; Falk, Gathie ; etc.
Issues in Clay: Western Canadian Sculpture, Students' Union Art Gallery, University of Alberta, Edmonton, May 4 - 29, 1981 / Alberta College of Art Gallery, Calgary, June 18 - July 24, 1981 / Medicine Hat Museum and Art Gallery, September 18 - 27, 1981 / etc.
boek